OPTIMALISASI PENAMBAHAN PROBIOTIK PROBIO-7 DENGAN KONSENTRASI YANG BERBEDA PADA PAKAN TERHADAP PERTUMBUHAN BENIH IKAN MAS (Cyprinus carpio) - Hesti Eunike Bau; Ridwan Tobuku; Jusuf R Manilapai (Jurnal Aquatik, 2026)
Aquaculture is the main basis for meeting animal protein needs through maximum productivity targets. The success of this sector is highly dependent on the synergy between feed management, water quality control, maintenance techniques, and the sustainability of quality seed supply. Fish growth and survival are highly dependent on the availability of high-quality feed, especially during the seed phase which requires a large protein intake. This research was conducted for 2 months at the oeluan fish seed center using an experimental method with a completely randomized design of 5 treatments and 3 replications: Control Treatment (without the addition of probio-7), Treatment A (addition of 10 ml probio-7/kg feed), Treatment B (addition of 15 ml probio-7/kg feed), Treatment C (addition of 20 ml probio-7/kg feed), Treatment D (addition of 25 ml probio-7/kg feed). The results of the study showed that the best absolute growth was in treatment D (addition of 25 ml probio-7/kg feed) with a value of (7.19 ± 0.39 gr) with a survival rate of 100% in each treatment. Keywods: Probio-7, Survival, Growth, Water Quality.